Post Molt Performance Parameters of Broiler Breeder Hens Associated with Molt Induced by Feed Restriction, High Dietary Zinc and Fasting - El-Deek, A.A.; Al-Harthi, M.A. (International Journal of Poultry Science, 2004)
Four hundred and eighty broiler breeder hens from a commercial flock of Hubbard broiler breeders was utilized in this experiment. The flock was reared for 19 weeks after which it was transferred to production houses. Egg production was commenced at the 24th week of age and egg production reached 80.2%. Hens at 57 weeks old and egg production of 46% were randomly selected from the production flock and were transferred to an open-house containing 15 floor pens (3 X 2.4 m.). Hens were randomly assigned to four force molting treatments, which were as follow: 1) feed and water restriction, 2) 20.000 ppm Zn as zinc oxide addition to the layer diet `16% CP`, 3) 30.000 ppm Zn as zinc oxide addition to the layer diet `16% CP`, and 4) fasting. The experimental period was divided into 4-periods, 1) From 1-day old till 14 day of age, 2) 15 till 32 days, 3) 33 to 58 days, and 4) 59 to 129 days of age. Results revealed that during the 1st experimental period, ZnO 3% and fasting treatment were significantly (p<0.05) higher in body weight losses (21%). Furthermore, ZnO addition to layer feed reduced feed consumption significantly. No effects of treatment were observed regarding the digestive system parameters. In the 2nd period of the study, body weights decreased with the ZnO 2%, feed restricted, and ZnO 3% (8.9, 4.9 and 4.4%) respectively. However, body weight in the fasting group increased (+14.5%). During the 3rd experimental period, body weight increased with all force molting treatments with the highest of the fasted group. No significant differences (p>0.05) were observed in the reproductive system parameters including ovary weight. However, oviduct weight of the ZnO 3% contributed the highest weight 3.53 g/1000 g body weight.